Editorial: Ebola outbreak: a public health emergency of international concern - Edward Eremugo Kenyi (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2019)
After nearly one year following the re-emergence of the Ebola Virus Disease (EVD) in the Democratic Republic of Congo (DRC), the World Health Organization (WHO) has declared the Ebola outbreak as a "public health emergency of international concern." This is only the fifth time in the history of the WHO that it has made such a declaration.